Two Different Behaviours of Mushroom Tyrosinase on the Impact of Different Concentrations of Thiophenol in Acidic Medium - ZOLGHADRI, S.; SABOURY, A.A. (Asian Journal of Chemistry, 2010)
The effect of thiophenol on the kinetic of coumaric acid hydroxylation by mushroom tyrosinase has been investigated at 20°C in 10 mM phosphate buffer solution, pH 5.3. The results show that thiophenol can activate or inhibit the cresolase activity of mushroom tyrosinase depending to the concentration of thiophenol. It was proposed that the enzyme has two distinct sites for thiophenol. The first one is a high-affinity activation site and the other is a low-affinity inhibition site. Activation of the enzyme in the low concentration of thiophenol arises from increasing the affinity of binding for the substrate as well as increasing the enzyme catalytic constant. The resulting fluorescence spectra at low concentrations of the ligand clearly demonstrate typical enhancement of aromatic emission in the presence of thiophenol referring to the more exposed residues after the addition of thiophenol. Although the tertiary structure of the enzyme changes due to the activation of mushroom tyrosinase by binding of thiophenol, but it is not accompanied by a change in the secondary structure of mushroom tyrosinase.